Generation of the Brucella melitensis ORFeome Version 1.1 - Dricot, Amélie; Rual, Jean-François; Lamesch, Philippe; Bertin, Nicolas; Dupuy, Denis; Hao, Tong; Lambert, Christophe; Hallez, Régis; Delroisse, Jean-Marc; Vandenhaute, Jean; Lopez-Goñi, Ignacio; Moriyon, Ignacio; et al.

(untitled) (Genome Research, 2004)
The bacteria of the Brucella genus are responsible for a worldwide zoonosis called brucellosis. They belong to the α-proteobacteria group, as many other bacteria that live in close association with a eukaryotic host. Importantly, the Brucellae are mainly intracellular pathogens, and the molecular mechanisms of their virulence are still poorly understood. Using the complete genome sequence of Brucella melitensis, we generated a database of protein-coding open reading frames (ORFs) and constructed an ORFeome library of 3091 Gateway Entry clones, each containing a defined ORF. This first version of the Brucella ORFeome (v1.1) provides the coding sequences in a user-friendly format amenable to high-throughput functional genomic and proteomic experiments, as the ORFs are conveniently transferable from the Entry clones to various Expression vectors by recombinational cloning. The cloning of the Brucella ORFeome v1.1 should help to provide a better understanding of the molecular mechanisms of virulence, including the identification of bacterial protein-protein interactions, but also interactions between bacterial effectors and their host's targets.